Brothers after war [videorecording (DVD)] - Rademacher, Jake; Rademacher, Isaac; Rademacher, Joseph, 1985- (SDG Releasing, 2025)
From Executive Producer Gary Sinise, in BROTHERS AFTER WAR, Jake Rademacher reconnects with his brothers and elite Soldiers and Marines he embedded with during the Iraq war. Intercutting footage past and present, he leads us on an insightful, humorous, and moving journey as we watch warfighters explore loss, meaning, and hope on their path from warfight to veteran.